Panoramic analysis of 2D dirubidium telluride monolayer benchmarking the DFT approach - G. Sneha; R. D. Eithiraj (Scientific Reports)
Abstract Through the DFT computations, the structural, vibrational, electronic, elastic, optical and thermal (thermoelectric, thermodynamic) properties of the two-dimensional Rb2Te monolayer are briefly contemplated. The Perdew-Bruke-Ernzerhof (PBE) form of generalized gradient approximation (GGA) functional in WIEN2k was deployed for the analysis of all these material properties. The trigonally crystallizing monolayer with an indirect band gap of 1.72 eV may be an upright single-layer that suffices distinct applications. ‘No negative’ phonon bands confirm the dynamical stability of the monolayer. The Rb2Te monolayer has large indirect band gap than Rb2S and Rb2Se. It exhibits mechanical stability with positive elastic constants satisfying the Born-Huang criterion for two-dimensional materials. The absorption coefficient spanning largely in the ultra-violet range makes the monolayer a congruous material for UV applications. Also, the thermoelectric figure of merit for p-type Rb2Te single-layer at room temperature is high (0.67) compared to the analogous series of compounds, that makes the monolayer a viable one for thermoelectric flexibility and experimental synthesis. The monolayer has high hole effective mass and D ratio. The obtained results aids in revealing the outstanding properties and excellent stability of the monolayer. Based on these findings the Rb2Te monolayer paves the way for promising applications in the fields of photovoltaics, thermoelectrics and UV-based applications.